Origin and diversification of Dicrocoeliidae (Neodermata, Trematoda) with the description of a new species of Euparadistomum, a parasite of Tropidurus torquatus (Squamata, Tropiduridae) in South America - Emmerich, Enzo [UNESP]; Aguiar, Julio Cesar Cenci de; Silva, Reinaldo José da (Elsevier, 2025)
A new digenean trematode species, Euparadistomum cisalpinai sp. n., is described parasitizing the gallbladder of Tropidurus torquatus from Brazil. A set of morphological features, including ovary shape, the oral/ventral sucker ratio, and the presence of cuticular papillae, distinguish the new species from other Euparadistomum species. Phylogenetic inferences using 28S rDNA sequences confirmed its placement within the family Dicrocoeliidae. Although some morphological variability was observed, COI sequences support conspecificity among the specimens. The origin of Dicrocoeliidae is estimated to date back to the Late Jurassic, a period marked by the fragmentation of Pangaea, the greatest radiation of insects, and the emergence of modern birds. These paleogeographic events, combined with the ecological traits of the hosts, likely served as key drivers of dicrocoeliid diversification. Additionaly, the opening of the North Atlantic, the dispersal of yangochiropteran bats, and the spread of Turdus birds significantly influenced the evolution of genera such as Lyperosomum, Anenterotrema, Metadelphis, and Lutztrema. This research provides key insights into the evolutionary and biogeographic history of Dicrocoeliidae, highlighting the pivotal role of host-parasite interactions and geographic events in shaping the diversification of these trematodes.